Hydrazinecarboxamide or Hydrazinecarbothioamide bearing small molecules as Dual inhibitor of Ras protein and Carbonic anhydrase enzyme as potential anticancer agent – AMLR approach based on docking energy. - saha, supriyo (Research in Biotechnology, 2014)